Causes and consequences of uncertainty about illness risk perceptions. (July 2020) - Orom, Heather; Biddle, Caitlin; Waters, Erika A; Kiviniemi, Marc T; Sosnowski, Amanda N; Hay, Jennifer L
We identified determinants of uncertainty about perceived risk judgments and demonstrated that uncertainty is associated with lower engagement in risk-reducing behavior. We found that people likely have metacognitive awareness of when their judgments are overly pessimistic, resulting in uncertainty and that question context (more constraints) and people's time orientation (future orientation) are associated with lower uncertainty. Uncertainty about conditioned risk judgments was associated with lower engagement in exercising and eating a healthy diet in order to reduce risk for heart disease. As a potential determinant of behavior, uncertainty about risk judgments merits further consideration for integration into theories of health behavior.